Myoepithelial carcinoma of the breast: A rare case presentation (Indian Journal of Case Reports, 2020)
Myoepithelial carcinoma (MC) remains a rarely encountered lesion of the breast. The few cases that have surfaced firmly document the histopathology and immunohistochemistry of this tumor. Here, we present a case of infiltrating MC of the breast in a 44-year-old female who presented with a painful lump. With the subsequent biopsy, the diagnosis was made on the basis of histopathological and immunohistochemistry. Histological examination showed spindle cells with moderate to marked nuclear atypia. Immunohistochemistry showed reactivity in the spindle cells for smooth muscle actin, cytokeratin (AE1/AE3), and p63, indicating a myoepithelial cell lineage of tumor cells. We suggest MCs of the breast be managed with an appropriate surgical clearance. A multidisciplinary approach is usually required.